Cyber Counseling: Definisi, Layanan, Pase dan Model - Muslima Muslima (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This article aims to provide information about advances in information and communication technology, the number of Internet users is increasing rapidly. Almost everyone in the world uses the internet in their daily life. Technological developments also affect the implementation of guidance and counseling services, especially in schools. In the era of globalization, there is a great demand for online counseling and cyber counseling by counselors and counseling teachers who can provide services regardless of distance and time. According to the survey results, cyber counseling services are considered effective because they provide opportunities for counselors and students to provide counseling that is not limited by distance and time. There are several stages of cyber counseling services used by counselors. Various models are used to conduct online consultations, including email, Facebook, asynchronous chat, riliv applications, video conferencing, mobile phones, and websites. Supervisors and counselors are expected to continue to improve their abilities in utilizing information and communication technology.